Spectrophotometric assay of oxymetazoline-HCl in pure form and in its pharmaceutical formulations using potassium permanganate.pdf - Basheer, Eman; Mohammed, Salim. (Libyan Journal of Science &Technology, 2022)
This study involves the development of two sensitive and reproducible spectrophotometric methods to determine oxymetazoline- HCl in pure form and its dosage forms. Both spectro-photometric methods were based on the reduction of potassium permanganate with oxymet-azoline- HCl. In method (A), oxymetazoline-HCl was reacted with an excess known amount of potassium permanganate in an acid solution of H2SO4 and the absorbance of unreacted potassium per-manganate was measured at 545 nm. In method (B) the oxidation reaction of oxymetazoline- HCl was carried out in an alkaline solution of sodium hydroxide and the absorbance of the resulting (MnO2) was measured at 610 nm. In method (A), the amount of potassium perman-ganate reacted corresponds to the oxymetazoline-HCl content and the intensity of absorb-ance decreased linearly with the concentration, while in method (B), the intensity of absorb-ance was increased linearly with concentration. Under optimum conditions, Beer’s law was found to be linear in the concentration range of 1.0-30 and 0.5-3.5 μg/ml with molar absorptivity 0.64×104 and 3.16×104 l.mol-1cm-1and cor-responding to Sandell's sensitivity values of 0.0448 and 0.0090 μg/cm2 for both methods (A) and (B), respectively. The detection limit (LOD) and quantification limit (LOQ) have also been estimated. Accuracy for pure OXM was calculated and found in the range -0.7% to 0.8% and-2.68% to 0.614%, while the precision (RSD) was <0.176% and <0.929% for method (A) and method (B), respectively. The two suggested methods (A) and (B) were successfully applied to the determination of oxymetazoline -HCl in bulk and its pharmaceutical preparations (drops and spray) with accurate and accepted results.